Asymptotic expansions for distribution of sums quasi-lattice random variables - Bikelis, Algimantas; Padvelskis, Kazimieras; Vaitkus, Pranas (Lietuvos matematikos rinkinys, 2011)
Althoug Chebyshev [3] and Edeworth [5] had conceived of the formal expansions for distribution of sums of independent random variables, but only in Cramer’s work [4] was laid a proper foundation of this problem. In the case when random variables are lattice Esseen get the asymptotic expansion in a new diﬀerent form. Here we extend this problem for quasi-lattice random variables.
Keywords: Edgeworth expansions; quasi-lattice distributions; Esseen expansions